Case report and literature review: Primary leiomyosarcoma of the penis - Hao, Yichang; Xia, Li; Lu, Min; Liu, Chenhong; Zhang, Fan; Yan, Ye; Huang, Yi; Zhang, Shudong (Frontiers in Surgery, 2023)
Background: In tumors of the penis, squamous cell carcinoma is the most common one, on the contrary, mesenchymal tumors are extremely rare. Leiomyosarcoma is a malignant mesenchymal tumor that derives from the smooth muscle lineage, and it shows a predilection for soft tissues and abdominopelvic organs compared to extremities. Primary leiomyosarcoma of the penis is a very rare disease of penile mesenchymal tissue. Case Report: 69-year-old man presented with progressively increasing painless mass at the penis in the last 3 years. Physical examination revealed the foreskin was too long, and there was a 2cm×2cm mass in the foreskin frenulum area, tough, mobile, painless and without skin ulceration or inguinal lymphadenopathy.Laboratory examination results were basically normal. MRI of the penis and pelvis was performed, demonstrating a 31×27×22mm heterogeneous mass in the distal penis, with hyperintense on DWI. Ultrasound examination showed no enlarged lymph nodes were detected in bilateral inguinal areas. First, the patient underwent resection of the penile mass, and three weeks later, the patient was readmitted and an extended resection was performed. The histopathology reported atypical spindle-shaped cells tumor with focal necrosis. Immunohistochemistry was positive for Desmin, smooth muscle antibody (SMA), Caldesmon and negative for S-100 and CD34, Ki-67 proliferation index was 70%+, P53 (wild-type). Morphological and immunohistochemically results were consistent with leiomyosarcoma. There is no definite identifiable factor as a causative factor for primary LMS of penis. It can be classified into superficial and deep depending upon invasion of the tunica albuginea. The presentation varies, presenting as a palpable mass, skin ulcer, or diffuse swelling. Conclusion: An immunohistochemical work up is very essential for rendering this rare diagnosis. Because of the small number of cases reported, the conclusions about treatment and prognosis are equivocal. For local tumor, the treatment is partial penectomy with negative margins of resection. When distant metastases have occurred, the tumor is generally considered incurable. Chemotherapy and radiation therapy have no scientific evidence yet to support them. The prognosis varies according to tumor size, location, and whether the tumor has metastatic or not. Due to the high rate of local recurrence, close follow-up should be given.